Members of Bitter Taste Receptor Cluster Tas2r143/Tas2r135/Tas2r126 Are Expressed in the Epithelium of Murine Airways and Other Non-gustatory Tissues - Liu, Shuya; Lu, Shun; Xu, Rui; Atzberger, Ann; Günther, Stefan; Wettschureck, Nina; Offermanns, Stefan (Frontiers in Physiology, 2017)
The mouse bitter taste receptors Tas2r143, Tas2r135 and Tas2r126 are encoded by genes that cluster on chromosome 6 and have been suggested to be expressed under common regulatory elements. Previous studies indicated that the Tas2r143/Tas2r135/Tas2r126 cluster is expressed in the heart, but other organs had not been systematically analyzed. In order to investigate the expression of this bitter taste receptor gene cluster in nongustatory tissues, we generated a BAC (bacterial artificial chromosome) based transgenic mouse line, expressing CreERT2 under the control of the Tas2r143 promoter. After crossing this line with a mouse line expressing EGFP after Cre-mediated recombination, we were able to validate the Tas2r143-CreERT2 transgenic mouse line and monitor the expression of Tas2r143. EGFP-positive cells, indicating expression of members of the cluster, were found in about 47% of taste buds, and could also be found in several other organs. A population of EGFP-positive cells was identified in thymic epithelial cells, in the lamina propria of the intestine and in vascular smooth muscle cells of cardiac blood vessels. EGFP-positive cells were also identified in the epithelium of organs readily exposed to pathogens including lower airways, the gastrointestinal tract, urethra, vagina and cervix. With respect to the function of cells expressing this bitter taste receptor cluster, RNA-seq analysis in EGFP-positive cells isolated from the epithelium of trachea and stomach showed expression of genes related to innate immunity. These data further support the concept that bitter taste receptors serve functions outside the gustatory system.